Nasal polyp fibroblasts modulate epithelial characteristics via Wnt signaling. Issue 12 (17th August 2018) - Dobzanski, Alex; Khalil, Syed Muaz; Lane, Andrew P.
Abstract : Background: While essential to the normal differentiation of ciliated airway epithelial cells, upregulated Wnt signaling in chronic rhinosinusitis with nasal polyps (CRSwNP) has been proposed to result in abnormal epithelial morphology and dysfunctional mucociliary clearance. The mechanism of epithelial Wnt signaling dysregulation in CRSwNP is unknown, and importantly cellular sources of Wnt ligands in CRSwNP have not yet been investigated. Methods: Human sinonasal epithelial cells (hSNECs) and human sinonasal fibroblasts (hSNFs) were collected from 34 human subjects (25 control and 9 CRSwNP) and differentiated as primary air‐liquid interface (ALI) and organoid co‐cultures. hSNECs were isolated to the apical compartment of the transwell and hSNFs were isolated to the basolateral compartment. After 21 days of ALI culture, ciliary expression and sinonasal epithelial morphology were examined by immunohistochemistry (IHC) and quantitative real‐time polymerase chain reaction (qRT‐PCR). An organoid model was used to evaluate proliferation of basal cells in presence of hSNFs. Results: Epithelial cells co‐cultured with CRSwNP‐hSNFs revealed significantly decreased ciliated cells, altered epithelial cell morphology, and increased colony forming efficiency compared to epithelial cells co‐cultured with control‐hSNFs. CRSwNP‐hSNFs showed significantly higher messenger RNA (mRNA) expression of canonical WNT3A . A Wnt agonist, CHIR99021, replicated CRSwNP‐hSNF co‐cultures, and treatment with the Wnt inhibitor IWP2 prevented abnormal morphologies. Conclusion: These results suggest that abnormal interactions between epithelial cells and fibroblasts may contribute to CRSwNP pathogenesis and supports the concept that dysregulated Wnt signaling contributes impairment to epithelial function in CRSwNP.